2003
DOI: 10.1182/blood-2002-12-3944
|View full text |Cite
|
Sign up to set email alerts
|

A novel EVI1 gene family, MEL1, lacking a PR domain (MEL1S) is expressed mainly in t(1;3)(p36;q21)-positive AML and blocks G-CSF–induced myeloid differentiation

Abstract: We have identified a novel gene MEL1 (MDS1/EVI1-like gene 1) encoding a zinc finger protein near the breakpoint of t(1; 3)(p36;q21)-positive human acute myeloid leukemia (AML) cells. Here, we studied the structure, expression pattern, and function of MEL1 in leukemia cells. In this study, we have identified 3 transcription start sites, 1 in exon 1 and 2 in exon 2, and 2 kinds of translation products, 170 kDa (MEL1) and 150 kDa (MEL1S). Notably, the 150-kDa band of MEL1S was detected mainly in the t(1;3)(p36;q2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
149
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 41 publications
(51 reference statements)
2
149
0
1
Order By: Relevance
“…Combining G-CSF with TSA treatment overcomes the blockade of G-CSF-induced differentiation in murine L-G3 cells induced by MEL1S expression We previously reported that the short form of MEL1 (MEL1S), a transcription factor that is specifically expressed in acute myeloid leukemia with the t(1;3) translocation, could block G-CSF-induced myeloid differentiation of L-G3, an IL-3-dependent myeloid leukemia cell line (Nishikata et al, 2003). Because MEL1S works as a transcriptional repressor in hematopoietic cells, including L-G3 cells ( Supplementary Figure 1), we initially investigated whether treatment of L-G3 cells with the HDAC inhibitor TSA prevents the blockade of G-CSF-induced differentiation by MEL1S expression.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Combining G-CSF with TSA treatment overcomes the blockade of G-CSF-induced differentiation in murine L-G3 cells induced by MEL1S expression We previously reported that the short form of MEL1 (MEL1S), a transcription factor that is specifically expressed in acute myeloid leukemia with the t(1;3) translocation, could block G-CSF-induced myeloid differentiation of L-G3, an IL-3-dependent myeloid leukemia cell line (Nishikata et al, 2003). Because MEL1S works as a transcriptional repressor in hematopoietic cells, including L-G3 cells ( Supplementary Figure 1), we initially investigated whether treatment of L-G3 cells with the HDAC inhibitor TSA prevents the blockade of G-CSF-induced differentiation by MEL1S expression.…”
Section: Resultsmentioning
confidence: 99%
“…To construct human MEL1S expression vectors, a FLAG-or a hemagglutinin (HA)-epitope tagged, short-form MEL1 lacking an N-terminal PR domain (MEL1S) (Mochizuki et al, 2000;Nishikata et al, 2003) was placed under the control of a cytomegalovirus (CMV) promoter in a mammalian expression vector pCMV26 (Sigma-Aldrich, St Louis, MO, USA) (pFLAG-MEL1S or pHA-MEL1S). To construct the human MEL1 expression vector, a HA-epitope tagged, long-form MEL1 with a PR domain (Mochizuki et al, 2000;Nishikata et al, 2003) was inserted into the pCMV26 (pHA-MEL1).…”
Section: Plasmid Constructionsmentioning
confidence: 99%
See 3 more Smart Citations